Hospital Management System: Logistic 2 (Vendor Portal, Audit Management, Vehicle Reservation System, Fleet Management, Document Tracking System): Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
A hospital management system (HMS) is a web-based platform solution that helps healthcareproviders manage daily operations more efficiently. It typically includes modules for patientregistration, appointment scheduling, medical records, inventory, supply, and billing andincludes subsystem logistics management, human resources, core management, andfinance. Hospital management logistics also involves managing the transportation of patients,medical supplies, and equipment. This includes managing the vehicle and ambulanceservices, organizing patient transfers, and coordinating the delivery of medical supplies andequipment to other healthcare facilities. Hospital Management Logistics Two is aboutmanaging resources efficiently and can help automate many of these tasks, making it easierto manage supply, equipment maintenance, and patient transportation; hospital managementlogistics 2 eliminates the possible harm in transactions, such as validating requests and otherdepartment request, to avoid the consumption risk of an anonymous person. Lack oftransaction monitoring, mistaken auditing of payment receipts, product information, anddocument information.As a result, the Project team has eliminated the issues. Validating requests: the project teamdevelops a request form to validate requests with the help of gathering their information. Thistechnique can avoid the consumption risk of an anonymous person. Transaction Monitoring:The project team developed a portal to improve and ensure a smooth flow of products andservices between suppliers, vendors, and other management. Auditing payment receipts: Theproject team developed payment receivables for their vendor and other management that areconnected to logistics and management. Provided document information: the project teamdeveloped tracking that can track where the documents are delivered to ensure that thecorrect goods are shipped, received, and billed.Our study encourages resolutions to make it easier to use. Hospital management logistics 2:effectively managing the supply of products and delivering them to the management. Hospitalmanagement logistics two can enhance visibility by implementing technology, adoptingautomation, and collaborating with stakeholders. Hospital management Logistics two alsoimproves transaction and functionalities of the system by integrating subsystems in thehospital management system, which provides some future that can post some requests forfinding vendors and posting assets for the hospital, transact supply products, have visibilityinto shipping and receiving processes, and track shipments, payment transactions, anddocuments for items.
Keywords: IT & Management